2023
DOI: 10.1088/1748-0221/18/05/p05019
|View full text |Cite
|
Sign up to set email alerts
|

Development of a radiation detector using a silicon photomultiplier and large Ce-doped Gd-Al-Ga-grant scintillator for gamma spectroscopy observations of radioactivation in a linear accelerator

Abstract: In this study, a radiation detector based on a silicon photomultiplier (SiPM) and large Ce-doped Gd-Al-Ga-grant (Ce:GAGG) scintillator was developed for the gamma spectroscopy observations of radioactivation from linear accelerators (LINACs). The calibration of the detector demonstrated a high energy resolution of 15.89% at 122 keV (gamma-ray emission energy of Co-57), 7.04% at 356 keV (gamma-ray emission energy of 133Ba), 6.17% at 511 keV (gamma-ray emission energy of Na-22), and 5.39% at 662 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Additionally, an annihilation peak was also observed. In a previous work in ref [15], a radiation detector was fabricated using Large cerium doped gadolinium aluminum gallium garnet (GAGG:Ce) scintillator coupled with SiPM for measuring radioactivation in the gantry head [15]. The results showed that the detector achieved an energy resolution of 5.39% at 662 keV and an energy-channel linearity of 0.98.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an annihilation peak was also observed. In a previous work in ref [15], a radiation detector was fabricated using Large cerium doped gadolinium aluminum gallium garnet (GAGG:Ce) scintillator coupled with SiPM for measuring radioactivation in the gantry head [15]. The results showed that the detector achieved an energy resolution of 5.39% at 662 keV and an energy-channel linearity of 0.98.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in previous studies, researchers combined SiPMs with larger scintillators to perform radioactivation measurements in LINACs. While they demonstrated the feasibility of radioactivation measurements in LINACs, there may still be some light loss due to the difference in the active areas of the scintillator and SiPM [15]. To address this mismatch, there is ongoing research on the design of light guides that can be used between the scintillator and SiPM to improve the coupling efficiency [16].…”
Section: Jinst 18 T09005mentioning
confidence: 99%